Oxytocin modulates hemodynamic responses to monetary incentives in humans. - Mickey, Brian; Heffernan, Joseph; Heisel, Curtis; Peciña, Marta; Hsu, David; Zubieta, Jon-Kar; Love, Tiffany (Psychopharmacology, 2016)
Rationale: Oxytocin is a neuropeptide widely recognized for its role in regulating social and reproductive behavior. Increasing evidence from animal models suggests that oxytocin also modulates reward circuitry in non-social contexts, but evidence in humans is lacking. Objectives: We examined the effects of oxytocin administration on reward circuit function in 18 healthy men as they performed a monetary incentive task. Methods: The blood oxygenation level-dependent (BOLD) signal was measured using functional magnetic resonance imaging in the context of a randomized, double-blind, placebo-controlled, crossover trial of intranasal oxytocin. Results: We found that oxytocin increases the BOLD signal in the midbrain (substantia nigra and ventral tegmental area) during the late phase of the hemodynamic response to incentive stimuli. Oxytocin's effects on midbrain responses correlated positively with its effects on positive emotional state. We did not detect an effect of oxytocin on responses in the nucleus accumbens. Whole-brain analyses revealed that oxytocin attenuated medial prefrontal cortical deactivation specifically during anticipation of loss. Conclusions: Our findings demonstrate that intranasal administration of oxytocin modulates human midbrain and medial prefrontal function during motivated behavior. These findings suggest that endogenous oxytocin is a neurochemical mediator of reward behaviors in humans-even in a non-social context-and that the oxytocinergic system is a potential target of pharmacotherapy for psychiatric disorders that involve dysfunction of reward circuitry.